A review of underwater acoustic metamaterials for underwater acoustic equipment - Zhu, Zhenjing; Hu, Ning; Wu, Junyi; Li, Wenxin; Zhao, Jiabao; Wang, Maofa; Zeng, Fanzong; Dai, Huajie; Zheng, Yongju (Frontiers in Physics, 2022)
Researchers use underwater acoustic equipment to explore the unknown ocean environment, which is one of the important means to understand and utilize the ocean. For acoustic equipment, the surface acoustic covering material is the premise to ensure and improve the performance of underwater acoustic communication, acoustic stealth, and sonar detection. Due to the limitations of mass density law and high hydrostatic pressure, traditional underwater sound absorption materials cannot effectively absorb low-frequency sound waves and have low efficiency of elastic energy conversion. The sound absorption effect is poor under low frequency and high hydrostatic pressure. In recent years, with the development of metamaterials, they are quickly introduced into the field of acoustic control. This paper reviews the basic characteristics, development history of sound absorption, sound insulation decoupling, and diffractive control metamaterials, then the existing problems and the future development direction of underwater sound absorption metamaterials are discussed.